Sistem Informasi Penyaluran Beras Miskin (Raskin) Kelurahan Desa Silau Malela Kabupaten Simalungun - Tambunan, Heru Satria; Sumarno, Sumarno; Gunawan, Indra (Jurnal Sistem Komputer dan Informatika (JSON), 2019)
Village Office Village Glare Malela Simalungun in the distribution mechanism distributing rice for the poor there are many processes of data collection using either a computer technology that uses Microsoft Exel, and conventionally sometimes encounter problems in the process of distribution transaction poor rice resulting in frequent occurrence of data redundancy and data collection which takes quite a long time. Therefore, the author wants to make the application of Information Systems Distribution of Rice Poor (Raskin) In the Village Office Village Glare Malela Simalungun using Adobe Dreamweaver CS6 application and database MySQL. System development method used is by the Waterfall method. Given this information system inputting, searching and reporting can be performed quickly and accurately because the data is stored securely and structured